`3^(x+4) = 6^(2x-5)`

To solve, take the natural logarithm of both sides.

`ln (3^(x+4)) = ln (6^(2x-5))`

To simplify each side, apply the logarithm rule `ln (a^m) =m*ln(a)` .

`(x+4)ln(3) = (2x-5) ln (6)`

`xln(3)+4ln(3) = 2xln(6) - 5ln(6)`

Then, bring together the terms with x on one side of...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

`3^(x+4) = 6^(2x-5)`

To solve, take the natural logarithm of both sides.

`ln (3^(x+4)) = ln (6^(2x-5))`

To simplify each side, apply the logarithm rule `ln (a^m) =m*ln(a)` .

`(x+4)ln(3) = (2x-5) ln (6)`

`xln(3)+4ln(3) = 2xln(6) - 5ln(6)`

Then, bring together the terms with x on one side of the equation. Also, bring together the terms without x on the other side of the equation.

`xln(3) - 2xln(6) = -4ln(3) -5ln(6)`

At the left side, factor out the GCF.

`x(ln(3) - 2ln(6)) =-4ln(3) -5ln(6)`

And, isolate the x.

`x = (-4ln(3) - 5ln(6))/(ln(3)-2ln(6))`

`x~~5.374`

**Therefore, the solution is `x~~5.374` .**